Lunar Tractive Forces and Renal Stone Incidence - Spyridon Arampatzis; George N. Thalmann; Heinz Zimmermann; Aristomenis K. Exadaktylos (Emergency Medicine International)
Background. Several factors are implicated in renal stone formation and peak incidence of renal colic admissions to emergency departments (ED). Little is known about the influence of potential environmental triggers such as lunar gravitational forces. We conducted a retrospective study to test the hypothesis that the incidence of symptomatic renal colics increases at the time of the full and new moon because of increased lunar gravitational forces. Methods. We analysed 1500 patients who attended our ED between 2000 and 2010 because of nephrolithiasis-induced renal colic. The lunar phases were defined as full moon ± 1 day, new moon ± 1 day, and the days in-between as “normal” days. Results. During this 11-year period, 156 cases of acute nephrolithiasis were diagnosed at the time of a full moon and 146 at the time of a new moon (mean of 0.4 per day for both). 1198 cases were diagnosed on “normal” days (mean 0.4 per day). The incidence of nephrolithiasis in peak and other lunar gravitational phases, the circannual variation and the gender-specific analysis showed no statistically significant differences. Conclusion. In this adequate powered longitudinal study, changes in tractive force during the different lunar phases did not influence the incidence of renal colic admissions in emergency department.